1998
DOI: 10.1002/(sici)1097-4644(19981201)71:3<375::aid-jcb6>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IGFBP‐5 binding to extracellular matrix and IGF‐I–stimulated DNA synthesis by a peptide fragment of IGFBP‐5

Abstract: Insulin-like growth factor binding protein-5 (IGFBP-5) is synthesized and secreted by smooth muscle cells (SMC). IGFBP-5 synthesis is stimulated five- to sixfold by IGF-I, and IGFBP-5 has been shown to augment IGF-I-stimulated DNA synthesis in this cell type. The ability of IGFBP-5 to augment the SMC response to IGF-I is dependent upon its binding to extracellular matrix. A highly charged region of IGFBP-5 that contains amino acids in positions 201-218 has been shown to mediate binding of IGFBP-5 to human fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Conversely, the low or absent expression in OSCC counterparts suggests, together with other studies, that the down‐regulation of IGFBP‐5 is an important event in OSCC, as it is in transformed mesenchymal cells and experimental breast cancers 8–12. Since the function of IGFBP‐5 varies in different tissues 6, 12–15, the executive roles of IGFBP‐5 in the proliferation, apoptosis, and migration of OSCC cells, as well as the interaction of IGFBP‐5 with environmental elements that might affect tumour progression, should be carefully addressed 4, 8. We have established that OECM‐1 cells stably express a low level of IGFBP‐5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the low or absent expression in OSCC counterparts suggests, together with other studies, that the down‐regulation of IGFBP‐5 is an important event in OSCC, as it is in transformed mesenchymal cells and experimental breast cancers 8–12. Since the function of IGFBP‐5 varies in different tissues 6, 12–15, the executive roles of IGFBP‐5 in the proliferation, apoptosis, and migration of OSCC cells, as well as the interaction of IGFBP‐5 with environmental elements that might affect tumour progression, should be carefully addressed 4, 8. We have established that OECM‐1 cells stably express a low level of IGFBP‐5.…”
Section: Discussionmentioning
confidence: 99%
“…The kinase activity of the putative IGFBP‐5 receptor is enhanced by IGFBP‐5, suggesting that it has a role in mediating IGF‐independent action 7. There is evidence that the IGFBP‐5 gene has a role as a potential suppressor gene through the inhibition of IGF‐I‐induced proliferation and migration of a variety of cells 4, 8–11. It has been shown that inhibition of the growth of MCF‐7 breast adenocarcinoma cells induced by anti‐oestrogen is associated with increased transcription of IGFBP‐5 12.…”
Section: Introductionmentioning
confidence: 99%
“…After 48 hours, the medium was removed and fresh medium was added with or without the IGFBP-5-blocking peptide for 24 hours. This IGFBP-5-blocking peptide (25) was kindly provided by D.R. Clemmons (Department of Medicine, University of North Carolina, Chapel Hill, North Carolina, USA).…”
Section: Generation Of Mk-pten Transgenic Mice the Mmtv-ltrmentioning
confidence: 99%